Effect of autogeneous self-healing on fatigue performance of ECC - Aw Yong, Wei Li (2016)
Self-healing phenomenon of cementitious composites has been noticed and discussed for a long time and several approaches have been proposed over the years. Since the invention of engineered cementitious composites (ECC) in the 1990s, much research have been conducted on self-healing behavior of this special type of cement-based materials because of its unique properties which maintain tight crack width of about 60μm that satisfied the stingy requirement of autogenous self-healing mechanism (Li and Herbert 2012). In this research, the author focus on the effect of autogenous self-healing on fatigue performance of ECC. While fatigue life of ECC specimens is designed to be the responding variable which reflects the effectiveness of self-healing, pre-damage level of ECC specimens and repeated healing condition are designed to be the manipulated variables of the experiments. Other properties such as crack width, flexural stiffness were also studied to provide a more thorough picture on self-healing behavior. Before the fatigue test, investigation on the most suitable cementitious composites mix design for robust self-healing was conducted. ECC mix design with 75% of cement content replaced by fly ash has demonstrated the best potential to achieve robust self-healing and was selected to be used throughout the fatigue load test. In summary, from the experiments, it is confirmed that fatigue performance of ECC can be improved by engaging autogenous self-healing conditioning. Further analyses and explanations will be discussed in the following chapters.